2017
DOI: 10.1051/0004-6361/201629930
|View full text |Cite
|
Sign up to set email alerts
|

Proxima’s orbit around α Centauri

Abstract: Proxima and α Centauri AB have almost identical distances and proper motions with respect to the Sun. Although the probability of such similar parameters is, in principle, very low, the question as to whether they actually form a single gravitationally bound triple system has been open since the discovery of Proxima one century ago. Owing to HARPS high-precision absolute radial velocity measurements and the recent revision of the parameters of the α Cen pair, we show that Proxima and α Cen are gravitationally … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 57 publications
6
123
0
Order By: Relevance
“…Wertheimer & Laughlin (2006) calculated the binding energy of the wide pair AB,C and found that it can be either positive or negative with roughly equal probability. The latest study by Kervella et al (2017), however, shows that the triple system is bound and that the eccentricity of the outer orbit is moderate, 0.42. Therefore this triple system has not been formed by unfolding.…”
Section: Unfoldingmentioning
confidence: 97%
See 1 more Smart Citation
“…Wertheimer & Laughlin (2006) calculated the binding energy of the wide pair AB,C and found that it can be either positive or negative with roughly equal probability. The latest study by Kervella et al (2017), however, shows that the triple system is bound and that the eccentricity of the outer orbit is moderate, 0.42. Therefore this triple system has not been formed by unfolding.…”
Section: Unfoldingmentioning
confidence: 97%
“…Wide binaries move so slowly that it is extremely difficult or impossible to test observationally whether they are gravitationally bound or just have common spatial motion and distance (Proxima Cen is a good example, Kervella et al 2017). Frequent occurrence of subsystems further complicates such tests.…”
Section: Introductionmentioning
confidence: 99%
“…• inclination of the orbit of Proxima Centauri around alpha Centauri AB (Kervella et al 2017). However, we do not consider these results to be in conflict since, in general, orbital motions in a hierarchical triple system are not expected to be coplanar (e.g., Muñoz & Lai 2015).…”
Section: A Possible Outer Belt At 30 Aumentioning
confidence: 99%
“…Doubts concerning the third member companionship of Proxima to α Cen AB have been raised on a number of occasions and it seems clear that, at best, Proxima is only marginally bound under standard Newtonian gravitational conditions [2,3,4], and that under alternative scenarios [5,6] it fits well within the domain of Modified Newtonian Dynamics (MOND). Kervella, Thevenin & Lovis [7] have most recently investigated the orbital dynamics of Proxima, and while they conclude that it is a gravitationally bound object to α Cen AB, their analysis, while claiming a "high degree of confidence" is still not fully convincing -indeed, they find, as with other earlier studies, that the odds of Proxima being a gravitationally bound object to α Cen AB are not much better than 50:50. Indeed, the conclusions drawn by Kervella, Thevenin and Lovis are all in the interpretation of the observational uncertainties, and in the modeling of complicated spectral effects such as extensive line blending, convective blueshift and gravitational redshift.…”
Section: Introductionmentioning
confidence: 83%
“…Indeed, the mass, radius and temperature are known to within an uncertainty of about 5% -its luminosity is a little less well constrained, but measured to an uncertainty of about 10%. Two values of the radius estimate are given in Table 1: the first value (INT) is that derived interferometrically by Demory et al [11], while the second (ML) is that given by Kervella, Thevenin & Lovis [7] based upon the recent 2MASS K s magnitude-radius calibration given by Mann et al [12]. In terms of fitting stellar evolutionary models to the observed data, Proxima is particularly interesting in that the only unknown quantity is its composition, and specifically its metallicity.…”
Section: Model Calculationsmentioning
confidence: 99%